Liquid–liquid interfacial slip induced layer instability in a thin polymer bilayer. (2nd September 2016) - Xu, Lin; Zhang, Huanhuan; Shi, Tongfei
Abstract: We investigate the influence of interfacial slip on the layer instability of thin polymer bilayer (polymethylmethacrylate (PMMA)/polystyrene (PS)/solid substrate). In the case of the bilayer system with a high molecular weight (Mw ) PMMA upper layer, it is found that the viscosity ratio of the two layers can greatly affect the instability modes of the polymer bilayer and there is a switchover of two different instability modes: (I) the dewetting of the PMMA upper layer on the PS under layer and (II) the dewetting of the PS under layer between the PMMA upper layer and the solid substrate. With the increase in the viscosity ratio between the PMMA upper layer and the PS under layer, the instability mode shifts from the instability mode I to the instability mode II. From our experimental results, it is found that the interfacial slip effect at the PMMA-PS interface is an important reason behind this switchover and the instability of the polymer bilayer system becomes a kinetically controlled one. However, in the case of the bilayer system with a lower Mw PMMA upper layer, the viscosity ratio of the two layers does not alter the instability mode of thin polymer bilayer and only the PMMA upper layer dewets on the PS under layers with different Mw . The instability of the polymer bilayer system is a thermodynamic controlled one. Graphical abstract: Highlights: The instability of thin polymer bilayer can become a kinetically controlled one. The instability modes can be shifted via the change of the viscosity ratio. The interfacial slip effect leads to the switchover of the instability modes.